PERAN SUPERVISI KEPALA SEKOLAH MELALUI PENDEKATAN DIREKTIF TERHADAP KINERJA GURU DALAM PROSES PEMBELAJARAN - Yessy Marlin; Sri Meliawati; Nila Prianti; Sufyarma Marsidin; Rifma Rifma; Tia Ayuningrum (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This study aims to examine the role of principal supervision through a directive approach to improving teacher performance in the learning process through a literature review. Educational supervision is an essential function of the principal that directly impacts the quality of learning. Based on the conceptual framework of Glickman, Gordon, and Ross-Gordon (2007), the directive approach is divided into two forms, namely directive control and directive informational, which are applied based on the level of commitment and level of abstraction of the teacher. The method used is a literature study by analyzing various scientific sources in the form of national journals, international journals, and relevant academic books. The results of the study indicate that the directive approach is effective when applied to novice teachers or teachers experiencing professional difficulties, where the principal plays an active role in providing direction, feedback, and clear performance standards. The implementation of targeted directive supervision has been proven to improve pedagogical competence, work motivation, and overall teacher performance. This study concludes that the effectiveness of directive supervision is highly dependent on the principal's sensitivity in diagnosing teacher needs and the consistency of the implementation of supervisory follow-up.